2004
DOI: 10.1158/1078-0432.ccr-03-0536
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Analysis and Prospective Validation of a Prognostic Model for Patients with High-Risk Primary Breast Cancer Receiving High-Dose Chemotherapy

Abstract: Purpose: We described previously a prognostic model for high-risk primary breast cancer patients receiving highdose chemotherapy (HDC). Such model included nodal ratio (no. involved nodes:no. dissected nodes), tumor size, hormone receptors, and HER2. In the present study we intended to test this model prospectively in a second patient cohort. In addition, we analyzed the long-term overall outcome of our HDC trials.Experimental Design: We analyzed all 264 patients enrolled since 1990 in our prospective trials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The optimal cutoff score of 2.41, as identified in the receiver operating characteristic curves, conferred on the model a sensitivity of 0.6, a specificity of 0.88, a positive predictive value of 0.65, a negative predictive value of 0.86, and an accuracy of 83%. The prognostic value of this score was confirmed externally (Nieto et al, 1999) and prospectively (Nieto et al, 2004).…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…The optimal cutoff score of 2.41, as identified in the receiver operating characteristic curves, conferred on the model a sensitivity of 0.6, a specificity of 0.88, a positive predictive value of 0.65, a negative predictive value of 0.86, and an accuracy of 83%. The prognostic value of this score was confirmed externally (Nieto et al, 1999) and prospectively (Nieto et al, 2004).…”
Section: Methodsmentioning
confidence: 74%
“…We retrospectively analysed tumour samples from patients who were prospectively enrolled in phase II and III trials of HDC for HRPBC at the University of Colorado between 1990 and 2001. A total of 234 patients were accrued in these studies, which were open to patients with 4 -9 positive axillary nodes (n ¼ 102) (Bearman et al, 1997;Moore et al, 2007) and 10 or greater positive nodes (n ¼ 132) (Nieto et al, 2004;Peters et al, 2005). Those trials, as well as the current retrospective review of tumour blocks, were approved by the Cancer Center Protocol Review Committee and the Institutional Review Board.…”
Section: Patient Populationmentioning
confidence: 99%
“…Furthermore, previous studies demonstrated that normalisation of an initial lymphocytopenia resulted in an improved clinical outcome in breast cancer patients treated with chemotherapy (Nieto et al , 2004; West et al , 2011). An elevated lymphocyte count has also significantly been associated with prolonged OS in patients with multiple myeloma and metastatic colorectal cancer (Leitch et al , 2007; Ege et al , 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The importance of lymphocytes has been demonstrated in several studies in which an increased infiltration of tumors with lymphocytes has been linked with improved outcomes in cancer patients [33][34][35][36]. Additionally, elevated peripheral blood lymphocyte counts have been correlated with prolonged survival in various types of cancer, whereas low peripheral blood lymphocyte counts have been linked with cancer progression and poor prognosis [22,[37][38][39][40]. A high dNLR might be caused by an elevated neutrophil count and/or a low lymphocyte count and likely reflects a more aggressive behavior of tumors.…”
Section: Discussionmentioning
confidence: 99%